Can CCL2 serum levels be used in risk stratification or to monitor treatment response in systemic sclerosis?. Issue 1 (29th June 2007) - Carulli, M T; Handler, C; Coghlan, J G; Black, C M; Denton, C P
Abstract : Objective: The chemokine CCL2 has been consistently found to be up-regulated in systemic sclerosis. To explore the potential value of serum CCL2 measurement in disease assessment, we have compared CCL2 levels with clinical phenotype and investigated effect of therapy on circulating CCL2. Methods: Serum samples from a well characterised cohort of 94 systemic sclerosis (SSc) patients, 16 patients with primary Raynaud phenomenon and 11 healthy controls were examined by ELISA. Our cohort of patients included 50 patients with limited cutaneous (lc)SSc (20 with lcSSc alone and 30 with pulmonary arterial hypertension-lcSSc), and 44 with diffuse cutaneous (dc)SSc, 30 of which had early-onset dcSSc. Results: Serum levels of CCL2 were increased in both major SSc subsets. In early stage dcSSc 18/30 (60%) cases demonstrated markedly elevated CCL2, and this was associated with anti-topoisomerase or anti-RNA polymerase I/III antibody reactivity, and with greater frequency of major organ-based complications. Elevation of CCL2 serum levels in the lcSSc subset was not associated with pulmonary arterial hypertension, although there was a trend for reduction following treatment with prostacyclin analogues or bosentan. Conclusion: These findings suggest that the CCL2/CCR2 axis is a potential therapeutic target in SSc, particularly in the early dcSSc subset. CCL2 measurement may be useful for risk stratification in early stage disease, but its value in disease monitoring is questionable.